CRISPR‐based point‐of‐care diagnostics incorporating Cas9, Cas12, and Cas13 enzymes advanced for SARS‐CoV‐2 detection. Issue 8 (1st June 2022) - Verma, Monika K.; Roychowdhury, Sanjana; Sahu, Bidya Dhar; Mishra, Awanish; Sethi, Kalyan K.
Abstract: An outbreak of the novel beta coronavirus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) first came to light in December 2019, which has unfolded rapidly and turned out to be a global pandemic. Early prognosis of viral contamination involves speedy intervention, disorder control, and good‐sized management of the spread of disease. Reverse transcription‐polymerase chain reaction, considered the gold standard test for detecting nucleic acids and pathogen diagnosis, provides high sensitivity and specificity. However, reliance on high‐priced equipped kits, associated reagents, and skilled personnel slow down sickness detection. Lately, the improvement of clustered regularly interspaced short palindromic repeat (CRISPR)‐Cas (CRISPR‐associated protein)‐based diagnostic systems has reshaped molecular diagnosis due to their low cost, simplicity, speed, efficiency, high sensitivity, specificity, and versatility, which is vital for accomplishing point‐of‐care diagnostics. We reviewed and summarized CRISPR–Cas‐based point‐of‐care diagnostic strategies and research in these paintings while highlighting their characteristics and challenges for identifying SARS‐CoV‐2.